A Non-APOE Polygenic Risk Score for Alzheimer's Disease Is Associated With Cerebrospinal Fluid Neurofilament Light in a Representative Sample of Cognitively Unimpaired 70-Year Olds. (29th January 2021) - Skoog, Ingmar; Kern, Silke; Najar, Jenna; Guerreiro, Rita; Bras, Jose; Waern, Margda; Zetterberg, Henrik; Blennow, Kaj; Zettergren, Anna
Abstract: The effect of Alzheimer's disease (AD) polygenic risk scores (PRS) on amyloid and tau pathophysiology and neurodegeneration in cognitively unimpaired older adults is not known in detail. This study aims to investigate non- APOE AD-PRS and APOE ε4 in relation to AD pathophysiology evaluated by cerebrospinal fluid (CSF) biomarkers in a population-based sample of 70-year olds. A total of 303 dementia-free individuals from the Gothenburg H70 Birth Cohort Studies were included. Genotyping was performed using the NeuroChip, and AD-PRS were calculated. CSF levels of amyloid-β (Aβ42), total tau (t-tau), phosphorylated tau (p-tau), neurogranin (Ng), and neurofilament light (NfL) were measured with enzyme-linked immunosorbent assay. Associations were found between non- APOE PRS and both NfL ( p = .001) and Aβ42 ( p = .02), and between APOE ε4 and Aβ42 ( p = 1e −10 ), t-tau ( p = 5e −4 ), and p-tau ( p = .002). Similar results were observed when only including individuals with CDR = 0, except for no evidence of an association between non- APOE PRS and Aβ42. There was an interaction between non- APOE PRS and Aβ42 pathology status in relation to NfL ( p = .005); association was only present in individuals without Aβ42 pathology ( p = 3e -4 ). In relation to Aβ42, there was a borderline interaction ( p = .06) between non- APOE PRS and APOE ε4 ; association was present in ε4 carriers only ( p = .03). Similar results were observed in individuals with CDR = 0 ( n = 246). In conclusion, among cognitively healthy 70-year olds from the general population, genetic risk of AD beyond the APOE locus was associated with NfL in individuals without Aβ42 pathology, and with Aβ42 in APOE ε4 carriers, suggesting these associations are driven by different mechanisms.